School Social Workers’ Perception of School Climate: An Ecological System Perspective - Hussein Soliman (International Journal of School Social Work, 2017)
Abstract The focus of this study was on school social workers' perception of school climate and to determine the factors that contribute to positive environment within the school. Using the ecological framework, the study examined the views of 315 school social workers concerning the current social climate in the state of Illinois by using a number of standardized—i.e., School Survey Crime and Safety Principle—and composite sub-scales. Correlation analysis presented significant associations among the study variables. A path analysis model was developed; it included one dependent variable (School Climate) and 6 independent variables (Resources, Exposure, Communication, Measures, and Environmental Limitations). Results show a significant model with CFI (Comparative Fit Index) of .999, CMI/df (Comparative Mean Index) of 1.16, and RMSEA (Root Mean Square of Approximation) of .2. Four paths were identified as significant in explaining direct and indirect effect with school climate.
Keywords: school climate; school social workers; ecological perspective